THE ROLE OF THE VILLAGE GOVERNMENT IN IMPROVING COMMUNITY SERVICES IN MATOMPI VILLAGE TOWUTI DISTRICT EAST LUWU REGENCY - Didin, Didin; Majid, Yusriaman; Guntur, Muhammad; Aina, Asri Nur (Universitas Negeri Makassar, 2024)
This study aims to find out the role of the village government in improving services and what are the obstacles of the Village Government in improving services to the community at the Matompi Village Office, Towuti District, East Luwu Regency. This study uses a descriptive qualitative approach. Data collection was used by observation, interview, and documentation techniques. The data obtained from the results of the research were processed using interactive model analysis, namely data condensation, data reduction, data presentation and conclusion drawn.The results of the study show that the role of the village government in improving services to the community at the Matompi Village Office, Towuti District, East Luwu Regency has been running well. This is shown by the role of the government as a regulator, facilitator, and dynamizer in improving community services. However, some of the obstacles experienced in realizing the government's role to improve public services include the size of the area, community awareness and socio-cultural conditions in Matompi Village, Towuti District, East Luwu Regency.